The disease burden of ILD at the global, regional, and national levels from 1990 to 2021, and projections until 2035: the 2021 Global Burden of Disease study - Lili Zhang; Lili Zhang; Junyi Zhang; Junyi Zhang; Yikun Guo; Jun Yan (Frontiers in Medicine)
BackgroundInterstitial lung disease (ILD) is an important component of the global disease burden and health challenges. This study aims to describe and analyze the global and regional disease burden of ILD, and predict future epidemiological trends.MethodsThe data from the 2021 Global Burden of Disease, Injury and Risk Factors (GBD) were used to conduct a secondary analysis on the incidence rate, mortality and disability adjusted life year (DALY) of ILD in 21 regions and 204 countries and regions from 1990 to 2021, stratified by time, space, gender, age and social demographic index (SDI). The Joinpoint regression model is used to calculate the average annual percentage change (AAPC). Using Bayesian Age Period cohort (BAPC) model to predict the global disease burden trend of ILD in 2035.ResultsIn 2021, the incidence, mortality, and DALY of ILD have all increased compared to before, while the ASIR, ASMR, and ASDR of ILD have also shown an upward trend. It is worth noting that the disease burden of males and the elderly is generally higher than that of females and other age groups. Meanwhile, cross-border inequality analysis shows that a disproportionate burden of ILD is concentrated in countries with higher SDI. Decomposition analysis shows that population growth and aging have become important influencing factors of ILD disease burden. The age period cohort effect indicates a roughly positive correlation between disease risk and age. Frontier analysis indicates that countries with higher SDI have greater potential for burden improvement. It is expected that the disease burden of ILD will increase by 2035.ConclusionThe disease burden of ILD remains an important health issue globally. Exploring disease differences among different regions, genders, and ages, analyzing the disease burden and future trends of ILD, is of great significance for developing targeted prevention strategies, optimizing healthcare accessibility, and improving diagnostic interventions.